2018
DOI: 10.1177/1088868318762647
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Contact Hypothesis: A Meta-Analysis on 20 Years of Research

Abstract: According to the extended contact hypothesis, knowing that in-group members have cross-group friends improves attitudes toward this out-group. This meta-analysis covers the 20 years of research that currently exists on the extended contact hypothesis, and consists of 248 effect sizes from 115 studies. The aggregate relationship between extended contact and intergroup attitudes was r = .25, 95% confidence interval (CI) = [.22, .27], which reduced to r = .17, 95% CI = [.14, .19] after removing direct friendship'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
182
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(189 citation statements)
references
References 80 publications
(127 reference statements)
3
182
0
4
Order By: Relevance
“…Intimate contact, like direct experiences of intergroup friendship, is particularly effective (see also Davies, Tropp, Aron, Pettigrew, & Wright, ). Their benefits and some of their psychological underpinnings are shared with indirect intergroup friendships (or “extended contact”; Paolini, Hewstone, Cairns, & Voci, ; for reviews, Turner, Hewstone, Voci, Paolini, & Christ, ; Zhou, Page‐Gould, Aron, Moyer, & Hewstone, ). Novel social network analyses now provide structural maps (Wölfer et al, ), and diary methods offer temporal analyses (Page‐Gould, ) of the positive downstream consequences of intergroup intimacy.…”
Section: Intergroup Contact Is Typically Positive Beneficial But Ofmentioning
confidence: 99%
“…Intimate contact, like direct experiences of intergroup friendship, is particularly effective (see also Davies, Tropp, Aron, Pettigrew, & Wright, ). Their benefits and some of their psychological underpinnings are shared with indirect intergroup friendships (or “extended contact”; Paolini, Hewstone, Cairns, & Voci, ; for reviews, Turner, Hewstone, Voci, Paolini, & Christ, ; Zhou, Page‐Gould, Aron, Moyer, & Hewstone, ). Novel social network analyses now provide structural maps (Wölfer et al, ), and diary methods offer temporal analyses (Page‐Gould, ) of the positive downstream consequences of intergroup intimacy.…”
Section: Intergroup Contact Is Typically Positive Beneficial But Ofmentioning
confidence: 99%
“…The second objective concerns the contact hypothesis (Allport, 1954;Pettigrew & Tropp, 2011;Zhou, Page-Gould, Aron, Moyer, & Hewstone, 2019). It proposes that, under most of conditions (namely that of equal status contact) more contact is related to more positive encounters and outcomes.…”
Section: Acculturation and Adaptationmentioning
confidence: 99%
“…Nevertheless, in spite of these successes, one major impediment to this strategy is that in many places in the world, intergroup contact is extremely uncommon and even unviable, especially for young children. An alternative strategy used to overcome this challenge is to present “indirect” situations of contact, that is, contact between in‐ and out‐group members that does not involve actual interactions between the subject and out‐group members (Zhou, Page‐Gould, Aron, Moyer, & Hewstone, ). Some of its forms are extended contact (Wright, Aron, McLaughlin‐Volpe, & Ropp, ), imagined contact (Crisp & Turner, ), and parasocial contact (Schiappa, Gregg, & Hewes, ), through which people become aware of friendships between in‐ and out‐group members by means of literature, imagination, or media, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Some of its forms are extended contact (Wright, Aron, McLaughlin‐Volpe, & Ropp, ), imagined contact (Crisp & Turner, ), and parasocial contact (Schiappa, Gregg, & Hewes, ), through which people become aware of friendships between in‐ and out‐group members by means of literature, imagination, or media, respectively. A great deal of research has demonstrated the benefits of indirect contact for intergroup attitudes and intergroup relationships among adults (for meta‐analyses, see Lemmer & Wagner, ; Zhou et al, ), as well as among children (Cameron, Rutland, & Brown, ; Vezzali, Capozza, Giovannini, & Stathi, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation